2012 IEEE International Workshop on Machine Learning for Signal Processing 2012
DOI: 10.1109/mlsp.2012.6349788
|View full text |Cite
|
Sign up to set email alerts
|

Sequential nonnegative tucker decomposition on multi-way array of time-frequency transformed event-related potentials

Abstract: Tensor factorization has exciting advantages to analyze EEG for simultaneously exploiting its information in the time, frequency and spatial domains as well as for sufficiently visualizing data in different domains concurrently. Event-related potentials (ERPs) are usually investigated by the group-level analysis, for which tensor factorization can be used. However, sizes of a tensor including time-frequency representation of ERPs of multiple channels of multiple participants can be immense. It is timeconsuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In this study, the fourth-order tensor consisted of the time-frequency results. It can be extracted by CPD (Cong et al 2014(Cong et al , 2012d):…”
Section: Tensor Decomposition Algorithmmentioning
confidence: 99%
“…In this study, the fourth-order tensor consisted of the time-frequency results. It can be extracted by CPD (Cong et al 2014(Cong et al , 2012d):…”
Section: Tensor Decomposition Algorithmmentioning
confidence: 99%
“…15 We have previously shown that the extracted components from the fourth-order ERP tensor by LRAS NTD and the benchmark algorithm referred to as HALS NTD 16 were highly similar. 17 However, the former algorithm was much faster than the latter. 17 This finding motivated us to study the fast (probability of presentation = 0.8) were considered standard stimuli.…”
Section: 4mentioning
confidence: 99%
“…17 However, the former algorithm was much faster than the latter. 17 This finding motivated us to study the fast (probability of presentation = 0.8) were considered standard stimuli. Happy and fearful expressions were rarely presented deviant stimuli (probability = 0.1 for each) (henceforth referred to as Fear and Happy for fearful faces and happy faces, respectively).…”
Section: 4mentioning
confidence: 99%
“…To solve the problem, Tucker decomposition, a higher‐order extension of traditional singular value decomposition (SVD) and Principal Component Analysis (PCA), has been used for multichannel signal analysis and showed advantages. 32 , 33 Tucker is a method used to estimate the ranks of an N‐order input tensor so that the high‐ and low‐frequency noises can be removed synchronously. 23 , 34 While its application in multichannel bioelectric signals is rare.…”
Section: Introductionmentioning
confidence: 99%